Foreign Trade and Macroeconomic Effects of Exports - TODOROVA, Tamara (Theoretical and Practical Research in Economic Fields; Vol 13 No 1 (2022): TPREF, Volume XIII, Issue 1(25), Summer 2022, 2022)
We find that the IS-LM model and the national income model reinforce each other in the context of exports and the export multiplier. Using simple differentiation techniques, we derive several relationships with respect to foreign trade. As predicted by Keynes, exports have a favorable effect on national income and the interest rate. Exports also increase the average price level and the exchange rate in the country. Through the mechanism of the export multiplier exports increase imports, savings, and consumption. A higher propensity to import reduces national income and fosters a negative trade balance. Similar is the effect of a higher exchange rate which discourages exports and encourages imports.